2018
DOI: 10.1371/journal.pone.0204488
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous glycine inhibits root elongation and reduces nitrate-N uptake in pak choi (Brassica campestris ssp. Chinensis L.)

Abstract: Nitrogen (N) supply, including NO3--N and organic N in the form of amino acids can influence the morphological attributes of plants. For example, amino acids contribute to plant nutrition; however, the effects of exogenous amino acids on NO3--N uptake and root morphology have received little attention. In this study, we evaluated the effects of exogenous glycine (Gly) on root growth and NO3--N uptake in pak choi (Brassica campestris ssp. Chinensis L.). Addition of Gly to NO3--N agar medium or hydroponic soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 60 publications
(95 reference statements)
0
4
0
Order By: Relevance
“…Moreover, animal-derived PHs could also contain high levels of thermostable amino acids such as glycine, alanine, hydroxylysine, hydroxyproline, and proline [41]. In particular, Han et al [50] demonstrated that exogenous glycine may inhibit root growth and indirectly decrease nitrate uptake in Brassica campestris. They ascribed the root growth inhibition to the increase of ethylene due to the glycine-dependent enhancement of the enzyme activities involved in its synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, animal-derived PHs could also contain high levels of thermostable amino acids such as glycine, alanine, hydroxylysine, hydroxyproline, and proline [41]. In particular, Han et al [50] demonstrated that exogenous glycine may inhibit root growth and indirectly decrease nitrate uptake in Brassica campestris. They ascribed the root growth inhibition to the increase of ethylene due to the glycine-dependent enhancement of the enzyme activities involved in its synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the observed decrease in most of the amino acid levels at the 48 h time-point following the GABA and VGB treatments might contribute to the inhibition of chestnut seed germination (Figure 6). At 120 h, however, only the VGB treatment induced a considerable increase in the accumulation of 10 amino acids ( Figure 6), which were reportedly negatively associated with root growth [13,37,[58][59][60]. Thus, VGB might have a specific role in inhibiting early primary root growth.…”
Section: Discussionmentioning
confidence: 97%
“…The exogenous supply of glycine can influence root morphology by inhibiting root elongation in pak choi (Brassica campestris ssp. Chinensis L.) [75]. Isolated AAs, including leucine (L-Leu), lysine (L-Lys), tryptophan (L-Trp), and glutamate (L-Glu), repress cell division and elongation in Arabidopsis primary roots [76], and its effect could be associated with auxin-and mitogen-activated protein kinase (MAPK) signaling [76,77].…”
Section: Root Architecturementioning
confidence: 99%